Study of Type VIII collagen in two species of marine sponges from Latakia coast - ابراهيم, خليل; أحمد قره علي,; ازدهار عمار , (Latakia University Journal -Biological Sciences Series, 2024)
Collagen Type VIII was analyzed in two species of Demosponges: Spongia officinalis and Hippospongia communis. Sponge samples were collected by free diving from depths of 5-10 metres, from the site of the Fanar Ibn Hani Marine protect area, next to the Higher Institute for Marine Research, during the years 2020 and 2021. Noticeable concentrations of this collagen were observed in marine sponges, where the average concentration is 10.625 mg/g in Spongia officinalis and 7.902 mg/g in Hippospongia communis, and the concentrations seemed close to each other. The technology of visible light spectroscopy was used in the analysis, which showed an easy and good way to study collagen in marine life.